A universal ligand mediated method for large scale synthesis of transition metal single atom catalysts - Hongzhou Yang (Nature Portfolio, 2019)
Single-atom catalysts are a promising class of catalytic materials, but general synthetic methods are limited. Here, the authors develop a ligand-mediated strategy that allows the large-scale synthesis of diverse transition metal single atom catalysts supported on carbon.